Reverse Engineering Representation Using an Image Processing Modification - Ahmed A. A. Duroobi (Al-Khwarizmi College of Engineering – University of Baghdad, 2019)
In the reverse engineering approach, a massive amount of point data is gathered together during data acquisition and this leads to larger file sizes and longer information data handling time. In addition, fitting of surfaces of these data point is time-consuming and demands particular skills. In the present work a method for getting the control points of any profile has been presented. Where, many process for an image modification was explained using Solid Work program, and a parametric equation of the profile that proposed has been derived using Bezier technique with the control points that adopted. Finally, the proposed profile was machined using 3-aixs CNC milling machine and a compression in dimensions process has been occurred between the proposed and original part so as to demonstrate the verification of the proposed method.